An Analysis of English Speaking Strategies of Hawkers at Tourism Spot - Baiq Ulfiya Hafizah; Muhammad Husnu; Usuluddin Usuluddin (Departement of Mathematics Education, 2024)
English is not only important for students to learn at school but can also be learned outside of school either through courses or autodidactically. Therefore, this study aims to analyze hawkers' English speaking learning strategies in tourist areas. This research is qualitative research with a case study method. The research data was collected through interviews with five hawkers to understand the strategies used in learning English especially speaking and a literature study to find out the types of language learning strategies used. The results showed that learning strategies used by hawkers in learning English, especially in speaking were 1) Hawkers' strategies in learning English for the first time, especially in speaking are social strategies and affective strategies. 2) Hawkers' strategies in learning English, especially speaking, are social strategies. 3) In terms of developing or improving pronunciation, they use social strategies and cognitive strategies. 4) In terms of strategies to improve vocabulary, they use memory strategies, social strategies, and cognitive strategies. 5) In terms of improving speaking fluency, they use social strategies and cognitive strategies. 6) In terms of improving accent, they used social strategies.